Introduction to Special Issue: An exploration of child and youth care pedagogy and curriculum - Jean-Pierre, Johanne; de Finney, Sandrina; Blanchet-Cohen, Natasha (International Journal of Child, Youth and Family Studies, 2020)
This special issue aims to explore Canadian pedagogical and curricular practices in child and youth care and youth work preservice education with an emphasis on empirical and applied studies that centre students’ perspectives of learning. The issue includes a theoretical reflection and empirical studies with students, educators, and practitioners from a range of postsecondary programs in Quebec, Ontario, Alberta, and British Columbia. The empirical articles use various methodologies to explore pedagogical and curricular approaches, including Indigenous land- and water-based pedagogies, ethical settler frontline and teaching practices, the pedagogy of the lightning talk, novel-based pedagogy, situated learning, suicide prevention education, and simulation-based teaching. These advance our understanding of accountability and commitment to Indigenous, decolonial, critical, experiential, and participatory praxis in child and youth care postsecondary education. In expanding the state of knowledge about teaching and learning in child and youth care, we also aspire to validate interdisciplinary ways of learning and knowing, and to spark interest in future research that recognizes the need for education to be ethical, critically engaged, creatively experiential, and deeply culturally and environmentally relevant.